Analysis of Technological Pedagogical and Content Knowledge (TPACK) to the Economics and Accounting Teachers - Kholifaturrohmah, Ramita; Mulasiwi, Cut Misni (Fakultas Ekonomi, Universitas Negeri Semarang, 2021)
In this study, a TPACK model was tested which describes the relationship between variables including Technological Knowledge (TK), Content Knowledge (CK), Pedagogical Knowledge (PK), Technological Content Knowledge (TCK), Pedagogical Content Knowledge (PCK), Technological Pedagogical Knowledge (TPK), and Technological Pedagogical and Content Knowledge (TPACK). Tests were done that obtain results regarding to the variables influencing TPACK the most. Respondents in this study were 61 economics and accounting teachers in SMA, SMK and MA Negeri Banyumas Regency. This study used a quantitative approach with a questionnaire technique. PLS with Smartpla 3.0 software was used as a analysis tool in this study. Based at the results of studies and data analysis, we can conclude that the variable that had the finest effect on TPACK was Technological Pedagogical Knowledge (TPK), thus the economics and accounting teachers in SMA, MA and SMK must be able to improve their TPK abilities. This is carried out by integrating various appropriate technologies in learning approaches such as learning strategies and designs so it can be able to build new interactions in improving the learning process.